Integrated Network Pharmacology and Metabolomics Analysis to Reveal the Potential Mechanism of Siwu Paste on Aplastic Anemia Induced by Chemotherapy Drugs - He D; Dan W; Du Q; Shen BB; Chen L; Fang LZ; Kuang JJ; Tang CY; Cai P; Yu R; Zhang SH; Huang JH (Dove Medical Press, 2022)
Dan He,1 Wan Dan,1 Qing Du,1 Bing-Bing Shen,1 Lin Chen,1 Liang-zi Fang,1 Jian-Jun Kuang,1 Chun-yu Tang,2 Ping Cai,1 Rong Yu,1,3 Shui-han Zhang,1 Jian-hua Huang1,3 1Hunan Academy of Chinese Medicine, Hunan University of Chinese Medicine, Changsha, Hunan, 410013, People's Republic of China; 2Hunan Times Sunshine Pharmaceutical Co., Ltd., Changsha, Hunan, 425007, People's Republic of China; 3Hunan Key Laboratory of TCM Prescription and Syndromes Translational Medicine Hunan, Changsha, Hunan, 410208, People's Republic of ChinaCorrespondence: Shui-han Zhang; Jian-hua Huang, Hunan Academy of Chinese Medicine, Hunan University of Chinese Medicine, Changsha, Hunan, 410013, People's Republic of China, Tel +86 13637400650 ; +86 18692265317, Email zhangshuihan0220@126.com; huangjianhua1985@163.comPurpose: This study aimed to reveal the multicomponent synergy mechanisms of SWP based on network pharmacology and metabolomics for exploring the relationships of active ingredients, biological targets, and crucial metabolic pathways.Materials: Network pharmacology, including TRRUST, GO, and KEGG, enrichment was used to discover the active ingredients and potential regulation mechanisms of SWP. LC-MS and multivariate data analysis method were further applied to analyze serum metabolomics profiling for discovering the potential metabolic mechanisms of SWP on AA induced by Cyclophosphamide (CTX) and 1-Acetyl-2-phenylhydrazine (APH).Results: A total of 27 important bioactive ingredients meeting the ADME (absorption, distribution, metabolism, and excretion) screening criteria from SWP were selected. Interaction networks were constructed and validated based on the 10 associated ingredients with the relevant targets. A total of 125 biomarkers were found by Metabolomics approach, which associated with the development of AA, mainly involved in amino acid metabolism and lipid metabolism. While SWP can reverse the above 12 metabolites changed by AA. Network analysis revealed the synergistic effects of SWP through the 43 crucial pathways, including Sphingolipid signaling pathway, Sphingolipid metabolism, Arginine and proline metabolism, VEGF signaling pathway, Estrogen signaling pathway.Conclusion: The study suggested that SWP is a useful alternative for the treatment of AA induced by CTX + APH. Its potential mechanisms are to improve hematopoietic microenvironment and promote bone marrow hematopoiesis therapies.Keywords: aplastic anemia, Siwu Paste, network pharmacology, metabolomics, integration analysis